Abdominal massage modulates gut microbiota and brain-gut peptides in insomnia model rats - Liu, Junchang; Aikebaier, Gulaisaer; Lu, Xusheng; Zhang, Xingping (Frontiers in Microbiology, 2025)
BackgroundAbdominal massage is a therapeutic intervention in traditional Chinese medicine for managing insomnia; however, its underlying mechanisms remain incompletely understood. This study aimed to investigate the effects of abdominal massage on the gut microbiota and brain-gut peptides in a rat model of insomnia from the perspective of the microbiota–gut–brain axis.MethodsForty-eight male Wistar rats were randomized into control, model, abdominal massage (Abd massage), and zolpidem groups (n = 12). An insomnia model was induced by intraperitoneal injection of 4-chloro-DL-phenylalanine (PCPA). The Abd massage group and the zolpidem group, respectively, received 14 days of abdominal massage and zolpidem treatment. Hippocampal histopathology was evaluated with hematoxylin and eosin (HE) staining. Serum levels of interleukin-1 beta (IL-1β), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), vasoactive intestinal peptide (VIP), growth hormone (GH), substance P (SP), and cholecystokinin-8 (CCK8) were measured by enzyme-linked immunosorbent assay (ELISA). The gut microbiota composition was examined using 16S rRNA sequencing.ResultsBehavioral experiments in a rat model of insomnia demonstrated that abdominal massage significantly extended sleep duration. The treatment alleviated histopathological damage in the hippocampus and regulated brain-gut peptide levels in both colon and brain tissues. Additionally, abdominal massage modulated gut microbiota structure, reducing the relative abundance of Bacteroidetes and Proteobacteria and increasing that of Firmicutes, Lachnospiraceae_NK4A136_group, Clostridia, and Clostridiales. Spearman correlation analysis revealed significant associations between microbial abundance and biochemical indicators. PICRUSt2 analysis further implicated carbohydrate metabolism, amino acid metabolism, and transcriptional regulation in the pathogenesis of insomnia.ConclusionThe results of this study demonstrate that abdominal massage ameliorates insomnia and increases sleep duration. This effect is associated with the regulation of brain-gut peptide levels and the restoration of gut microbiota diversity and structure. These findings suggest that the microbiota-gut-brain axis may be involved in the therapeutic mechanism of abdominal massage for insomnia.